Brain energetics during the sleep–wake cycle. (December 2017) - DiNuzzo, Mauro; Nedergaard, Maiken
Highlights: Cerebral aerobic glycolysis and lactate levels are elevated during wakefulness. Sleep is metabolically expensive and increases oxygen–glucose utilization stoichiometry. Noradrenergic tone targets brain ionostatic, glymphatic and metabolic functions. Astrocytes affect state-specific presynaptic/postsynaptic neuronal activity and plasticity. Abstract : Brain activity during wakefulness is associated with high metabolic rates that are believed to support information processing and memory encoding. In spite of loss of consciousness, sleep still carries a substantial energy cost. Experimental evidence supports a cerebral metabolic shift taking place during sleep that suppresses aerobic glycolysis, a hallmark of environment-oriented waking behavior and synaptic plasticity. Recent studies reveal that glial astrocytes respond to the reduction of wake-promoting neuromodulators by regulating volume, composition and glymphatic drainage of interstitial fluid. These events are accompanied by changes in neuronal discharge patterns, astrocyte–neuron interactions, synaptic transactions and underlying metabolic features. Internally-generated neuronal activity and network homeostasis are proposed to account for the high sleep-related energy demand.